Faktor-Faktor Yang Memengaruhi Risiko Produksi Bawang Putih Di Indonesia - Solehah, Putri Febrilla; Fariyanti, Anna (Forum Agribisnis, 2024)
Garlic productivity in Indonesia is still low and fluctuates every year. The productivity fluctuations indicate production risks. This research aims to analyze the factors that influence the productivity and risks of garlic production in Indonesia. The data used in this study is secondary data from the Agricultural Census. Locations of this research were chosen purposively. They are in the three largest production centers, namely Central Java, West Nusa Tenggara, and East Nusa Tenggara. The total sample is 305 farmer respondents from 333 farmer respondents surveyed by the Statistic Center Agency. The method of analysis used in this study is production function with the Just and Pope model approach. Multiple linear regression analysis for the productivity function is estimated through the Ordinary Least Squares (OLS) method, whereas, for the production risk function, estimation is conducted using the Maximum Likelihood Estimation (MLE) method. The results showed that the risk level of garlic production in Indonesia was high. Factors significantly increased productivity, including seeds, labor, the dry season, and climate change. Meanwhile, factors that significantly reduced productivity are organic fertilizers and SP36 fertilizers. The risk-inducing production factor is climate change, while the risk-reducing factors are pest attacks and liquid pesticides. To boost productivity, farmers can cultivate garlic during the dry season, increase the use of high-quality seedlings and labor, and reduce the application of organic and SP36 fertilizers. To mitigate production risks, farmers can enhance the use of liquid pesticides following recommended usage standards.